2018
DOI: 10.1080/01616412.2018.1503992
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ghrelin, nesfatin-1 and irisin levels of serum and brain after acute or chronic pentylenetetrazole administrations in rats using sodium valproate

Abstract: Statistically significant alterations were detected in the serum and brain levels of these three peptides in both the PTZ-induced chronic epilepsy model and acute seizure model. The results of this study may suggest that the increase in FNDC5/irisin and nesfatin-1 levels, and the decrease in ghrelin levels may contribute to seizure pathophysiology. However, further studies are needed in order to confirm our hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In summary, in previous studies, significant alterations were reported in ghrelin [15][16][17][18] , irisin 20 , FNDC5/irisin 18 , and nesfatin-1 16,18 levels. Despite this, there is also lack of evidence of whether these four neuropeptide levels are altered with drug resistant temporal lobe epilepsy (DRTLE) or not.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…In summary, in previous studies, significant alterations were reported in ghrelin [15][16][17][18] , irisin 20 , FNDC5/irisin 18 , and nesfatin-1 16,18 levels. Despite this, there is also lack of evidence of whether these four neuropeptide levels are altered with drug resistant temporal lobe epilepsy (DRTLE) or not.…”
Section: Introductionmentioning
confidence: 62%
“…Increased 15 or decreased 16,17 ghrelin levels have been reported in studies on epilepsy patients. In a previous study, significantly decreased ghrelin levels in the brain and serum were found in acute PTZ-induced seizures; and PTZ kindling models, in rats 18 . It was suggested that ghrelin has antiepileptic 27 and neuroprotective 28 properties.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations